Reviews. Issue 2 (1st September 2015) - Herzog, Carrie; Zhen, Willa; Fernandez, Jeff; Stutter, Natalia; Gebbels, Maria; Irimiás, Anna; Palm, Elin; Wilkinson, Samantha; Ormond, Meghann; Iarmolenko, Svitlana; Manzo, Lidia K.C.
Everyone Eats: Understanding Food and Culture, E. N. Anderson (2014) 2nd ed., New York and London: New York University Press, 362 pp., ISBN: 9780814760062, p/bk, £14.56; ISBN: 9780814770146, h/bk, £47.56The Cultivation of Taste: Chefs and the Organization of Fine Dining, Christel Lane (2014) Oxford: Oxford University Press, 384 pp., ISBN: 9780199651658, h/bk, £30.00Vodka Politics: Alcohol, Autocracy and the Secret History of the Russian State, Mark Lawrence Schrad (2014) New York, NY: Oxford University Press, 512 pp., ISBN: 9780199755592, h/bk, £22.99Street Food: Culture, Economy, Health and Governance, Ryzia De Cassia Vieira Cordoso, Michéle Companion and Stefano Roberto Marras (eds) (2014) Abingdon: Routledge, xviii+281 pp., ISBN: 9781138023680, h/bk, £85.00Foodies and Food Tourism, Donald Getz, Richard Robinson, Tommy Andersson and Sanja Vujicic (2014) Oxford: Good Fellow Publishers Ltd, 239 pp., ISBN: 9781910158005, p/bk, $48.00/£29.99Heritage in the Digital Era: Cinematic Tourism and the Activist Cause, Rodanthi Tzanelli (2013) Abingdon: Routledge, xv + 247 pp., ISBN: 9781415643801, h/bk, £90.00Binational Human Rights: The U.S.-Mexico Experience, William Paul Simmons and Carol Mueller (eds) (2014) Philadelphia, PA: University of Pennsylvania Press, 300 pp., ISBN: 9780812246285, h/bk, £36.00Contemporary Adulthood and the Night-time Economy, Oliver Smith (2014) Basingstoke: Palgrave Macmillan, 204 pp., ISBN: 9781137344519, h/bk, £58Disruptive Tourism and its Untidy Guests: Alternative Ontologies of Future Hospitalities, Soile Veijola, Jennie Germann Molz, Olli Pyyhtinen, Emily Höckert and Alexander Grit (2014) Basingstoke: Palgrave Macmillan, viii+167 pp., ISBN: 9781137399496, h/bk, £60.00Identity and Intercultural Exchange in Travel and Tourism, Anthony David Barker (ed.) (2015) Bristol: Channel View, xi+220 pp., ISBN: 9781845414627, p/bk, £29.95Market Place : Food Quarters, De sign and Urban Renewal in London, Susan Parham (2012) Newcastle upon Tyne: Cambridge Scholars Publishing, xi + 332 pp., ISBN: 9781443841726, h/bk, £49.99